Clinical and Pathological Findings of Renal Biopsy in Children: Outcomes from a Single Center Over 27 Years - Shin Ae Lee; Min Sun Kim; Soon Chul Kim; Dae-Yeol Lee (Korean Society of Pediatric Nephrology, 2017)
Purpose To classify the results of renal biopsy in pediatric patients and to compare pathological findings with clinical features. Methods This study included data of 318 children who underwent renal biopsy at our hospital between December 1987 and November 2014. Biopsy specimens were examined histopathologically using light, immunofluorescence, and electron microscopy. Results Asymptomatic urinary abnormalities was the most common clinical diagnosis (35.9%), followed by nephrotic syndrome (29.3%), and acute glomerulonephritis (18.0%). Glomerular disease was identified in 98.1% of the renal biopsy specimens. The most common primary cause of glomerulonephritis was IgA nephropathy, with gross hematuria in 61.9% of the patients, hypertension in 14.2%, proteinuria >1.0 gm/24-hr in 33.3%, and impaired renal function in 3.6% patients. Conclusion The most common clinical diagnosis was asymptomatic urinary abnormalities, with primary glomerular disease being the most common renal biopsy finding, and IgA nephropathy the most common histopathological lesion. This study provides a 27-year overview of pediatric renal disease at our center and underlines the importance of renal biopsy for accurate diagnosis and proper management.